Possible risk factors of opaque bubble layer and its effect on high-order aberrations after small incision Lenticule extraction - Yang, Shan; Wang, Heng; Chen, Zhengyu; Li, Ying; Chen, Youxin; Long, Qin (Frontiers in Medicine, 2023)
To evaluate the possible risk factors of opaque bubble layer (OBL) formation in small incision lenticule extraction (SMILE) surgery and its effects on visual quality.Methods: Fifty-six eyes from 28 patients were included in this study. The preoperative parameters and intraoperative designs were recorded. Corneal high-order aberrations (HOAs), point spread function (PSF), and modulation transfer function (MTF) were measured using iTrace at pre-operation, 1 week, 1 month, and 3 months after SMILE. Generalized Estimating Equation and Linear Mixed Effects Model were employed for statistical analysis.The mean OBL area in SMILE surgery was 2.75%±1.25%. The patients were divided into groups based on whether the OBL was greater than the mean group or less than the mean group. Compared to the group with a smaller OBL area, the group with the larger OBL area had steeper corneal curvature and thinner cap thickness, the OBL area was positively correlated with the preoperative keratometry (𝑟 = 0.21, 𝑃=0.04) and preoperative spherical value (𝑟 = 0.47, 𝑃 = 0.01). The group with the larger OBL area induced more corneal SA and trefoil at 1 week postoperatively, but the difference was not significant at 1 month and 3 months postoperatively.A steep corneal curvature, thin cap thickness, and high preoperative spherical value are possible risk factors for OBL formation in SMILE surgery. The OBL increased the ocular and corneal HOAs postoperatively for a short period (1 week), while it did not affect the long-term outcomes.